Variation in feed utilisation by sheep undergoing compensatory growth following underfeeding with and without additional dietary nitrogen in western China - Philp, Joshua; Komarek, Adam M.; Pain, Sarah; Bellotti, William D. (Commonwealth Scientific and Industrial Research Organisation, 2016)
Small mixed farming systems in developing economies often rely on compensatory growth to recover livestock weight lost during seasonal feed shortages; however, deficit feed management may continue to affect the capacity of livestock to efficiently use feeds even after adequate feeding has resumed. Accordingly, we compared the difference in liveweight gain and feed utilisation over time in Tan weaner sheep in western China, during a period of ad libitum compensatory feeding after alternative feed deficit scenarios. During the feed deficit period, sheep were offered, at 80% maintenance requirements, corn straw, corn grain and lucerne hay in a respective ratio of either 80 : 20 : 0 (S1 ration: metabolisable energy = 7 MJ/kg DM, crude protein = 40 g/kg DM) or 55 : 20 : 25 (S2 ration: metabolisable energy = 8 MJ/kg DM, crude protein = 65 g/kg DM) for 20 days. All sheep were then offered an ad libitum supply of the S2 ration for a further 20 days, during which DM digestibility (DMD), energy intake and liveweight was measured and compared at 5-day intervals. Results indicated that sheep previously fed the S1 ration were not able to digest as much of the ad libitum S2 ration as those previously fed the S2 ration, experiencing significantly lower DMD, energy intake and average daily weight gain. The difference in the effect of the two restrictive feeding treatments on the digestibility of the ad libitum S2 ration gradually decreased over time, indicative of a recovery adaptation during ad libitum feeding period. The rate of DMD recovery post-realimentation was greater in the S1 sheep, likely due to their significantly lower DMD values immediately following underfeeding. We concluded that the comparatively higher nutritive value of the S2 ration sustained rumen digestive function throughout the restrictive feeding period, permitting sheep to commence re-feeding under conditions that are more favourable. Additionally, it is evident that reliance on livestock winter rations typical in western China, as expressed by the S1 ration, degraded ruminant digestive conditions to such an extent that feed was used with reduced efficiency even after being supplied in adequate quantities.